Calibrating and modelling of statistical delay for signalized intersections at al-Nasiriyah City in Iraq - Alshnawa, Abdullah Hayal Khalaf; Amiruddin Ismail,; Essa, Alla Jaber; Hussein, Ameer Abdul Adheem (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this paper develops an empirical delay model for delay prediction by taking lane group parameters to make delay model in the field where delay have considered very important measure that effects at signalized intersection because of relation of delay with performance of signalized intersection, lost travel time, fuel consumption, feasible of movement, discomfortable of drivers also, it is considered the primary measure to determine the level of service at signalized intersection. The main aim of this study is to make a field delay model at signalized intersection by using microsimulation software to calibrate data and using statistical software (SPSS) to create model. The methodology of the study is made by using video recording and manual collected data by taken three biggest signalized intersections where the collection data was very challenged specifically speed forward and uncontrollable drivers and others factors. Sidra Intersection 6.0 is described as an advanced micro-analytical model with a lane-by-lane method and a vehicle drive-cycle model that is used to estimate capacity and performance measures through an iterative method. Calibration of the software is very necessary to find accurate model that can be described the field delay. Multiple Linear Regression analysis (MuLRa) has been generally statistical method to create a model. It has been taken into consideration in the modelling of delay at signalized intersection and adjusted R² is 80% with multi factors that effect on field delay. Vehicle speed has been improved very significance level and impact factor on delay at signalized intersection by lane group experimental method and this finding very important for all simulation software should be taken that in the accounts.